Attention Centrality and Audience Fragmentation: An Approach for Bridging the Gap Between Selective Exposure and Audience Overlap. (27th August 2021) - Barnidge, Matthew; Diehl, Trevor; Sherrill, Lindsey A; Zhang, Jiehua
Abstract: Scholarship on audience fragmentation typically takes one of two approaches: The micro-level analysis of individuals' selective exposure to partisan news, or the macro-level analysis of audience overlap. To bridge the gap between these levels of analysis, we introduce the concept of attention centrality as a set of macro-to-micro measures that characterize how individual news media selection is situated within networks of public attention. Relying on an online panel survey conducted in the United States (N = 1, 493), we examine the relationship between three indicators of respondents' attention centrality (closeness, betweenness, and reach) and the partisan valence of their news selections. The study finds different patterns of results for the three indicators of attention centrality, indicating that partisan news media are not uniformly isolated to the periphery of public attention. Results are discussed in light of conversations about selective exposure and audience overlap in the United States and around the world.